Advanced Metallization Concepts for p‐type Silicon Metal‐Wrap‐Through (MWT) Solar Cells. Issue 1 (30th December 2013) - Hendrichs, Max; Thaidigsmann, Benjamin; Lohmüller, Elmar; Nold, Sebastian; Clement, Florian; Biro, Daniel; Rech, Bernd; Preu, Ralf
Abstract The development of cost‐effective and highly efficient solar cells is a primary goal of current research activities. In this work we investigate two different metallization concepts based on screen‐printing technology that are aimed at achieving increased cell conversion efficiency of p‐type silicon metal‐wrap‐through (MWT) solar cell structures. The first approach is the reduction of the pad area of the external rear n‐type contacts. Furthermore a multilayer metallization concept is presented that allows for the decoupling of the rear external n‐type contact and the p‐type silicon base. In this context new pastes for via metallization are investigated—namely low‐temperature silver–polymer pastes. The second approach is the optimization of the metallization layout of MWT solar cells to minimize cost of ownership. Therefore the number of contact rows, the finger width, and the number of n‐type contact pads per contact row are varied methodically by using analytical simulations. The results are compared with experimental data. Both approaches show a potential for a further conversion efficiency increase of p‐type silicon MWT solar cells.